Right place. Right time. Right tool: guidance for using target analysis to increase the likelihood of invasive species detection - Jeffrey T. Morisette; Jamie K. Reaser; Gericke L. Cook; Kathryn M. Irvine; Helen E. Roy (Biological Invasions, 2020)
In response to the National Invasive Species Council’s 2016–2018 Management Plan , this paper provides guidance on applying target analysis as part of a comprehensive framework for the early detection of and rapid response to invasive species (EDRR). Target analysis is a strategic approach for detecting one or more invasive species at a specific locality and time, using a particular method and/or technology(ies). Target analyses, which are employed across a wide range of disciplines, are intended to increase the likelihood of detection of a known target in order to maximize survey effectiveness and cost-efficiency. Although target analyses are not yet a standard approach to invasive species management, some federal agencies are employing target analyses in principle and/or in part to improve EDRR capacities. These initiatives can provide a foundation for a more standardized and comprehensive approach to target analyses. Guidance is provided for improving computational information. Federal agencies and their partners would benefit from a concerted effort to collect the information necessary to perform rigorous target analyses and make it available through open access platforms.